Design of one-dimensional phononic crystals comprising robust Fano edge modes as a highly sensitive sensor for alcohols - Fathy, Hamza Makhlouf; El-Sherbeeny, Ahmed M.; Al Zoubi, Wail; Hajjiah, Ali; Elsayed, Hussein A.; Semeda, Ramadan; Ismail Fathy, Moataz; Abukhadra, Mostafa R.; Mehaney, Ahmed (Frontiers in Physics, 2024)
This work introduces various designs of phononic crystals (PnCs), referred to as topological phononic crystals (TPnCs), as novel, stable, and high-performance sensing tools. Meanwhile, we introduce the concept of the topological edge state to address the discrepancies between theoretical predictions and experimental results of PnC sensors. Consequently, the design of a PnC sensor structure that maintains high stability amidst fluctuations in layer manufacturing and deformations during construction represents the mainstay of our study. Notably, the numerical findings demonstrate the stability of the proposed sensor in the presence of various geometric changes. In addition, we assess the effectiveness of several periodic PnC designs in sensing the physical properties of fluids, specifically alcohols like butanol. Accordingly, temperature sensing of butanol is conducted over a wide range (170°C–270°C) by monitoring the displacement of Fano resonance modes. In this regard, the proposed PnC structure demonstrates an impressive sensitivity of 119.23 kHz/°C. Furthermore, our design achieves a high-quality factor and figure of merit of 378.23 and 1.085, respectively, across the temperature range of 170°C–230°C. These outcomes are promising for the development of ultrasensitive thermal sensors. Ultimately, our research provides valuable insights into the creation of highly sensitive and stable temperature sensors suitable for a range of industrial applications.